PRARANCANGAN PABRIK ADIPONITRIL DARI ASAM ADIPAT DAN AMONIAK DENGAN KAPASITAS 100.000 TON/TAHUN - , M WAHYU ADITIA; , Dr. Ir. Edia Rahayuningsih, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Adiponitrile (ADN) or hexanedinitrile is an organic compound with the molecular formula CN(CH2)4CN produced as an intermediate product for the manufacture of 1,6-hexamethylenediamine or diaminohexane which is the main raw material for Nylon 6,6. Adiponitrile industrial development opportunities in Indonesia is very large due to the world demand for Nylon 6,6 is increasing every year, and considering that to date there has not been recorded adiponitrile factory has been established in Indonesia. The plant is planned to operate for 330 days/year with a production capacity adiponitrile 100,000 tons/year. The main raw material required are 136.515,97 tons/year adipic acid 99% and 35.000,76 ammonia 99,5% tons / year. The process of the reaction is in the gas phase at a temperature of 390oC and a pressure of 2 atm with boron phosphate as catalyst in a fluidized bed reactor. In general, the process of making adiponitrile steps are as follows: 1) The reaction between adipic acid and ammonia with boron phosphate as catalyst in a fluidized bed reactor, 2) Separation of ammonia from the mixture with cooling process, 3) Separation of water in the distillation tower (MD- 01) , 4) Purification of the product in the distillation tower (MD-02). As a support, the utility unit was established to supply the needs of the cooling water as much as 385.45 tons/hour, 674.5 kVA electricity, and compressed air up to 100 m3/hr. The plant is planned to set up in Palembang, South Sumatra province, with consideration of raw material oriented. Palembang region close to the ammonia industry, PT. Pusri, and close to the port that facilitate the procurement of raw materials adipic acid imported from China as well as facilitate the marketing of products adiponitrile later. Plant location close to the river, so the water source for the unit comes from the river water utility. Calculation of economic evaluation results of fixed capital required is $ 67,265,923.43 and working capital of $ 83,421,403. At 100% production capacity, obtained ROI before tax amounted to 51.22%, 25.61% ROI after tax, before tax POT 1.63 years, 2.81 years after tax POT with BEP of 42.46%, SDP 28, DCFRR 37% and 13.54%. Based on consideration of the evaluation results, the adiponitrile plant with a capacity of 100,000 tonnes / year is worth to be studied further.